Dollar Index Analysis Using Double Zigzag to Predict an Exchange Rate ( USD / ERU) - Thaer Mirdan, Alyaa; Kadhum Jawad, Kamal (Iraqi Journal for Administrative Sciences, 2024)
The research aims to introduce the Double Zigzag wave, which is one of the Elliott waves, as well as introducing the US dollar index in the forex market, and how to use this wave as a method for wave trading and highlighting some of the methods used by traders to predict the direction of foreign exchange rates. The research problem was embodied in the dialectical statement of the relationship between the zigzag bilateral wave and its ability to predict the direction of the exchange rates (USD / ERU) based on the analysis of the dollar index through a set of questions, most notably knowing the extent of the effect of the zigzag wave in predicting the movement of the dollar index in particular and the effect of those waves on the movement of currency prices in the forex market in general. The research reached a set of conclusions, the most important of which is that the zigzag binary Elliott waves can predict foreign exchange rates by analyzing the dollar index of the major currency pair selected for the research sample (ERU / USD) for the period 2010-2021.